The Degree to which Teachers of the First Three Grades in Ajloun Governorate Schools Possess Educational Competencies to Apply the Principles of UDL from Their Point of View - Ananbeh, Fadwa Mohammad AbedAlQader (Journal of Educational and Psychological Sciences, 2022)
This study aimed to identify the degree to which teachers of the first three grades possess educational competencies to apply the principles of UDL from their point of view, the study used the descriptive analysis approach, questionnaire has been used it consisted from (28) paragraph, the sample of study consisted from (150) female and male teachers. However, the finding of study showed that the degree to which teachers of the first three grades possess educational competencies to apply the principles of UDL from their point of view was moderated with average (3.64. out of 5). The finding also showed there were a significant difference at (α ≤ 0.05) in the degree to which teachers of the first three grades possess educational competencies to apply the principles of UDL from their point of view refers to variable of teacher's years of experience in favor of less than 10 years. Furthermore, there weren’t any significant differences according to the level of classroom. In light of these results, the Researcher recommended to inclusion of the principles of comprehensive design for learning in pre-service teacher qualification programs.
Keywords: Educational Competencies; Principles of UDL; Teachers of the First Three Grades